Heparanase-enhanced shedding of syndecan-1 by myeloma cells promotes endothelial invasion and angiogenesis - Purushothaman, Anurag (American Society of Hematology, 2010)
Heparanase enhances shedding of syndecan-1 (CD138), and high levels of heparanase and shed syndecan-1 in the tumor microenvironment are associated with elevated angiogenesis and poor prognosis in myeloma and other cancers. To explore how the heparanase/syndecan-1 axis regulates angiogenesis, we used myeloma cells expressing either high or low levels of heparanase and examined their impact on endothelial cell invasion and angiogenesis. Medium conditioned by heparanase-high cells significantly stimulated endothelial invasion in vitro compared with medium from heparanase-low cells. The stimulatory activity was traced to elevated levels of vascular endothelial growth factor (VEGF) and syndecan-1 in the medium. We discovered that the heparan sulfate chains of syndecan-1 captured VEGF and also attached the syndecan-1/VEGF complex to the extracellular matrix where it then stimulated endothelial invasion. In addition to its heparan sulfate chains, the core protein of syndecan-1 was also required because endothelial invasion was blocked by addition of synstatin, a peptide mimic of the integrin activating region present on the syndecan-1 core protein. These results reveal a novel mechanistic pathway driven by heparanase expression in myeloma cells whereby elevated levels of VEGF and shed syndecan-1 form matrix-anchored complexes that together activate integrin and VEGF receptors on adjacent endothelial cells thereby stimulating tumor angiogenesis.